Current treatment of hypertension in patients with coronary artery disease recommended by different guidelines. (22nd January 2016) - Aronow, Wilbert S
Abstract : Introduction: It is important to know how to treat hypertension in patients with coronary artery disease (CAD). The reason for the review was to update this treatment and to discuss the 2015 American Heart Association/American College of Cardiology/American Society of Hypertension 2015 guidelines of treatment of hypertension in patients with CAD. Areas covered: Studies between 1968 and 2015 were reviewed on treatment of hypertension in patients with CAD using a Medline search, and studies between 1977 and 2015 were reported. Hypertension should be treated with beta blockers and ACE inhibitors or angiotensin receptor blockers (ARBs). Long-acting nitrates are effective antianginal and anti-ischemic drugs. Calcium-channel blockers (CCBs) may be added if angina persists despite beta blockers and long-acting nitrates. The 2015 guidelines recommend that the blood pressure should be < 140/90 mm Hg in patients aged ≤ 80 years and the systolic blood pressure < 150 mm Hg if they are ≥ 80 years. Expert opinion: Hypertension in patients with CAD should be treated with beta blockers and ACE inhibitors or ARBs. Long-acting nitrates are effective antianginal and anti-ischemic drugs. CCBs may be added if angina persists despite beta blockers and long-acting nitrates. The blood pressure should be < 140/90 mm Hg in patients aged < 80 years and the systolic blood pressure < 150 mm Hg if they are ≥ 80 years.